Scalable Production of a Few-Layer MoS2/WS2 Vertical Heterojunction Array and Its Application for Photodetectors - Xue, Yunzhou; Zhang, Yupeng; Liu, Yan; Liu, Hongtao; Song, Jingchao; Sophia, Joice; Liu, Jingying; Xu, Zaiquan; Xu, Qingyang; Wang, Ziyu; Zheng, Jialu; Liu, Yunqi; et al. (ACS nano, 2016)
Vertical heterojunctions of two two-dimensional (2D) transition metal dichalcogenides (TMDs) have attracted considerable attention recently. A variety of heterojunctions can be constructed by stacking different TMDs to form fundamental building blocks in different optoelectronic devices such as photodetectors, solar cells, and light-emitting diodes. However, these applications are significantly hampered by the challenges of large-scale production of van der Waals stacks of atomically thin materials. Here, we demonstrate scalable production of periodic patterns of few-layer WS2, MoS2, and their vertical heterojunction arrays by a thermal reduction sulfurization process. In this method, a two-step chemical vapor deposition approach was developed to effectively prevent the phase mixing of TMDs in an unpredicted manner, thus affording a well-defined interface between WS2 and MoS2 in the vertical dimension. As a result, large-scale, periodic arrays of few-layer WS2, MoS2, and their vertical heterojunctions can be produced with desired size and density. Photodetectors based on the as-produced MoS2/WS2 vertical heterojunction arrays were fabricated, and a high photoresponsivity of 2.3 A·W–1 at an excitation wavelength of 450 nm was demonstrated. Flexible photodetector devices using MoS2/WS2 heterojunction arrays were also demonstrated with reasonable signal/noise ratio. The approach in this work is also applicable to other TMD materials and can open up the possibilities of producing a variety of vertical van der Waals heterojunctions in a large scale toward optoelectronic applications.